Análise da relação entre sentimento do investidor e estrutura de capital - Macedo, Luciana Alencar Firmo (2017)
In the face of various speculations in the stock market, strong economic and political changes in the Brazilian and world scenario, companies need a better management of the resources available for their decision-making, especially with regard to sources of financing, with a view to the guarantee of a better condition of participation/permanence in the market. With support in these discussions, this research aims to analyze the relation between the investor sentiment in the structure of capital of the Brazilian companies. For this, I analysed a sample that involved all non-financial companies listed in B3 (Bolsa Brasil Balcão) during the period from 2005 to 2016. In order to answer the research problem, the methodology consisted in the construction of an Investor Sentiment Index (ISI) based on the methodology developed by Baker and Wurgler (2006; 2007). In addition, I used alternative indexes such as Consumer Confidence Index (CCI) and Industry Confidence Index (ICI) developed by the Getúlio Vargas Foundation, allowing the observation of the impact of the investor sentiment on the capital structure of Brazilian companies. In the estimation of the investor sentiment, I used the multivariate technique of Principal Component Analysis to capture the common component of four different proxies for market behavior. In this way, I found evidenced that the investor sentiment index was sensitive to the market oscillations, accompanying the euphoria and crisis effects of the Brazilian market. As for the relationship between the investor sentiment and the capital structure, I found a negative interaction, in which Brazilian companies tend to be less indebted at moments of high market sentiment, corroborating Oliver and Mefteh (2010). I Also verified that the measure of the investor sentiment index was significant with a good part of the related variables. Regard to the managers' overconfidence, represented by the family companies, the interaction between these variables was sought to identify the existence of a greater sensitivity of the capital structure in relation to the effect of the investor sentiment and the possible impacts that the excess of confidence exerts on the indebtedness decisions of the companies. Thus, I evidenced that the level of indebtedness of the family companies had a negative relation with the investor sentiment. This result can be justified by the managers' too much confidence, once they prefer to make their indebtedness decisions without observing the market signals, that is, they perceive a greater control by the managers in relation to being more confident and not being influenced by the sensitivity of the market.